A taxonomic assessment of novel and remarkable fungal species in Didymosphaeriaceae (Pleosporales, Dothideomycetes) from plant litter - Tennakoon, Danushka S.; Thambugala, Kasun M.; Silva, Nimali I. de; Suwannarach, Nakarin; Lumyong, Saisamorn (Frontiers in Microbiology, 2022)
Fungal taxonomy has a long history and changed significantly in the last few decades. Most recent studies have witnessed that morphology incorporated with DNA-based molecular analyses emerge as the main research tool for fungal species identification. During field surveys, some interesting Didymosphaeriaceae species were found from plant litter in China and Thailand. Morphology combined with phylogenetic analyses (Bayesian and maximum likelihood) of ITS, LSU, SSU, tef1-α and tub2 loci were used to identify the fungal taxa. Three new species and six new host records are described. The new species, Montagnula acaciae, Paraconiothyrium zingiberacearum and Paraphaeosphaeria brachiariae can be distinguished from other species of the respective genera in their distinct size differences (ascomata, asci and ascospores) and DNA sequence data. The new host records, Montagnula jonesii, P. fuckelii, Spegazzinia deightonii and S. tessarthra are reported from Ficus benjamina, Dimocarpus longan, Hedychium coronarium and Acacia auriculiformis respectively for the first time. As well as, Paraconiothyrium archidendri, P. brasiliense are reported for the first time on Magnolia sp. in China. Moreover, Paraconiothyrium rosae is synonymized under P. fuckelii based on close phylogeny affinities and morphological characteristics. In-depth morphological descriptions, micrographs and phylogenetic trees to show the placement of new taxa are provided.